PENDIDIKAN KARAKTER PANCASILA PADA ERA NATIVE DEMOCRACY - Utami Dewi SA (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2019)
Since the proclamation of independence, Pancasila has become the basis of the state as well as a way of looking at the self and future of the Indonesian nation. The turbulent implementation of the Pancasila between the extreme right and the left has resulted in a phobia for the Indonesian nation towards its own ideology. In fact, in the era of native democracy, which is currently stretching, a strong ideological basis is needed as a source of internalization of values in education. Formulating character education derived from the values of the Pancasila will produce a golden generation of 2045 as the peak momentum of a century of Indonesia's independence celebration. Rejuvenation or refreshment of the perspective on Pancasila is absolutely necessary by returning to the philosophical and historical basis of the basic formulation of the country itself. Thus, Pancasila will truly become a source of essential and fundamental values for the development of the nation, state and character of Indonesian people as a whole.Key Words: character education, pancasila, native democracy